Validity and reliability Measurement of TIMSS 2011 test in mathematics across school location and supervising authority in Jordan - Al-Samaky, Lutfi Fawzi (Journal of Educational and Psychological Sciences, 2020)
The purpose of this study is to examine the measurement invariance of TIMSS mathematics test for eighth grade across school location and the supervising authority (Ministry of Education, UNRWA) in Jordan. To achieve this, the researcher used the analytical descriptive approach to analyze the test results for Jordanian 8th graders who participated in the TIMSS study in 2011. Specifically, the responses of 547 students to 34 items in booklet eight and nine were analyzed. Seven items were excluded because the skewness index is ​​greater than 2 and the kurtosis index is greater than 7. The data of the remaining 27 items were analyzed by using Confirmatory Factor Analysis (CFA) and Multiple Groups Confirmatory Factor Analysis (MGCFA) through the statistical program (AMOS 22). To judge the suitability of the test factorial structure the following goodness-of-fit indices in Structural equation modeling (SEM) were used: Chi Square (χ2) test was a statistically significant value of 468.167 and a good comparison index was CFI statistically significant value of 0.934 which is greater than 0.80 and the square of the mean root error approx. The results showed that there is no Configural invariance according to the location of the school (countryside, city), and the values ​​of the χ2 were a statistical function and its value is 822.858 and a good comparison index CFI is a statistical function and its value is 0.918 which is greater than 0.80 and the mean square root of the approximate error RMSEA is a statistic function and its value is 0.024 which is less than 0.08 and a root index The mean of the standard residual squares of SRMR is statistically significant and its value is 0.0408 which is less than 0.09. The results showed that there is no Metric (or weak) invariance according to the location of the school (countryside, city), the values ​​of the χ2 were a statistical function and its value is 861.321 and a good comparison index CFI is a statistical function and its value is 0.913 which is greater than 0.80 and the average square error of the approximate error RMSEA is a statistical function whose value is 0.024 and is less than 0.08 and an index The root mean standard SRMR squares are 0.0432 and less than 0.09. The results also showed that there was no Scalar (or strong) invariance according to the location of the school (countryside, city), and the values ​​of the χ2 were a statistical function and its value was 910.730 and a good comparison index CFI was a statistical function and its value is 0.903 which is greater than 0.80 and the average square of the approximate error root RMSEA statistically significant value and 0.025 which is less than 0.08 and an index The root mean standard SRMR squared is 0.0430 and is less than 0.09. The results showed that there is no Configural invariance in the supervising authority (Ministry of Education, UNRWA), and the values ​​of the χ2 were a statistically significant value of 833.660 and a good comparison index CFI was a statistical function with a value of 0.898 which is greater than 0.80 and an average square of the root error of approximate RMSEA statistically significant value of 0.028 which is less than 0.08 The mean index of the standard residual squares SRMR is statistically significant, and its value is 0.0351, which is less than 0.09. The results showed that there is no Metric (or weak) invariance for the supervising authority (Ministry of Education, UNRWA), and the values ​​of the χ2 were a statistically significant value of 890.903 and a good comparison index CFI was a statistically significant value of 0.883 which is greater than 0.80 and the square of the mean root error of approx. RMSEA statistically significant value of 0.029 which is less than 0.08 and the mean root index of the standard residual squares SRMR are statistically significant and have a value of 0.0620 which is less than 0.09. The results also showed that there is no Scalar (or strong) invariance of the supervising authority (Ministry of Education, UNRWA), and the values ​​of the χ2 were a statistical function and its value is 993.653 and a good comparison index CFI is a statistical function and its value is 0.854 and it is greater than 0.80 and the square of the average root error of RMSEA is a statistic function and its value is 0.033 which is less than 0.08 and the mean root index of the standard SRMR squares are statistically significant and their value is 0.0634 which is less than 0.09.